2021
DOI: 10.32598/fdj.4.38
|View full text |Cite
|
Sign up to set email alerts
|

Study of Lag of Accommodation After Using a Smartphone

Abstract: Background and Objectives: With the pervasive use of digital devices, especially smartphones, concerns about their harmful effects on vision has increased. The aim of the present study was to evaluate the effect of long-term activity with a smartphone on the accuracy of lag of accommodation of two eyes. Methods: In this cross-sectional study, 27(16 females and 11 males) students and staff (23 students and 4 staff) of the Iran University of Medical Science with a Mean±SD age of 25.29±4.72 years, with a visual a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…Therefore, the pixel format of letters on liquid-crystal display (LCD) displays causes a grater lag compared to the printed materials (23). Likewise, Zamari et al (28) reported a high lag of accommodation after one hour of smartphone use, and the finding is consistent with other studies.…”
Section: Accuracy Of Accommodationsupporting
confidence: 85%
“…Therefore, the pixel format of letters on liquid-crystal display (LCD) displays causes a grater lag compared to the printed materials (23). Likewise, Zamari et al (28) reported a high lag of accommodation after one hour of smartphone use, and the finding is consistent with other studies.…”
Section: Accuracy Of Accommodationsupporting
confidence: 85%